Cor, educação e casamento: tendências da seletividade marital no Brasil, 1960 a 2000 - Carlos Antonio Costa Ribeiro; Nelson do Valle Silva (Universidade do Estado do Rio de Janeiro, 2009)
The article analyzes trends in marital selectiveness among blacks, browns, and whites in Brazil, using data from 1960, 1980, and 2000. Given that the educational system expanded and racial inequalities decreased over the years, the article aims to investigate to what extent these trends are related to the reduction in barriers to interracial marriage, as observed during the period. The authors thus analyze marriage patterns in couples of different color and schooling. The reduction in barriers to interracial marriage is independent of the parallel decrease in couples with different educational levels. Such barriers have become less common in all groups, except for those with the most education; in other words, the odds of marriage between husbands and wives with any level of university education increased from 1960 to 2000, corresponding to an increase in the barrier to marriage between highly educated individuals and less educated partners. Nevertheless, the overall trend was towards a decrease in barriers to interracial and inter-educational marriages from 1960 to 2000. In other words, there are steadily fewer impediments to interracial and inter-educational marriages in Brazil.